Ghrelin stimulates neurogenesis in the dorsal motor nucleus of the vagus - Zhang, Weizhen (Blackwell Science Inc, 2004)
Ghrelin, a gastric peptide hormone, has been reported to regulate growth hormone secretion and energy homeostasis. Here we show that ghrelin promotes neural proliferation in vivo and in vitro in the rat dorsal motor nucleus of the vagus (DMNV). Ghrelin receptor mRNA and immunoreactivity were detected in tissues from DMNV. Systemic administration of ghrelin (130 nmol kg(−1)) significantly increased 5-bromo-2′-deoxyuridine (BrdU) incorporation in the DMNV in adult rats with cervical vagotomy (BrdU positive cells; from 27 ± 4 to 69 ± 14 n = 5, P < 0.05). In vitro, exposure of cultured DMNV neurones to ghrelin significantly increased the percentage of BrdU incorporation into cells in both dose-dependent (10(−9)–10(−6)m), and time-dependent (6 h to 48 h) manners. Ghrelin significantly increased voltage-activated calcium currents in isolated single DMNV neurones from a mean maximal change of 141 ± 26 pA to 227 ± 37 pA. Upon removal of ghrelin, calcium currents slowly returned to baseline. Blocking L-type calcium channels by diltiazem (10 μm) significantly attenuated ghrelin-mediated increments in BrdU incorporation (n = 5, P < 0.05). Ghrelin acts directly on DMNV neurones to stimulate neurogenesis.